On the timing of climate agreements - Robert C. Schmidt; Roland Strausz (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2014)
A central issue in climate policy is the question whether long-term targets for green- house gas emissions should be adopted. This paper analyzes strategic effects related to the timing of such commitments. Using a two-country model, we identify a redistributive effect that undermines long-term cooperation when countries are asymmetric and side payments are unavailable. The effect enables countries to shift rents strategically via their R&D efforts under delayed cooperation. In contrast, a complementarity effect stabi- lizes long-term cooperation, because early commitments in abatement induce countries to invest more in low-carbon technologies, and create additional knowledge spillovers. Con- trasting both effects, we endogenize the timing of climate agreements.
Keywords: D62; F53; H23; Q55; 330; climate treaty; abatement; long-term cooperation; spillover; strategic delay